CYP2C19 polymorphism has no influence on rabeprazole‐based sequential therapy. Issue 4 (15th December 2017) - Lin, Tsung‐Jung; Lee, Hsi‐Chang; Lin, Chih‐Lin; Wang, Chung‐Kwe; Chen, Kuan‐Yang; Wu, Deng‐Chyang
Summary: Background: The aim of this prospective study was to evaluate the impact of cytochrome P450 2C (CYP2C19) and interleukin‐1β (IL‐1β) polymorphisms on the efficacy of Helicobacter pylori ( H. pylori ) eradication by using rabeprazole‐based sequential therapy. Methods: From March 2013 to May 2014, total 87 H. pylori ‐infected patients were recruited to receive a 10‐day of sequential therapy. We had excluded 4 patients from analysis because of incomplete compliance. We performed either follow‐up endoscopy or 13 C‐urea test to assess the treatment response. CYP2C19 and IL‐1β genotypes were analyzed to investigate the impact on H. pylori eradication. Results: On the whole, the eradication rate of H. pylori was 80.72% (67/83). The rates of H. pylori eradiation were 79.31% in extensive metabolizers (EM) and 81.48% in non‐EM according to the CYP2C19 genotypes. The rates of H. pylori eradiation were 80.00% in the normal acid secretion group and 81.03% in the low acid secretion group according to the IL‐1β genotypes. After multivariable logistic regression analysis, both genotypes of CYP2C19 and IL‐1β were not significantly independent factors of H. pylori eradication. Conclusions: Both CYP2C19 and IL‐1β polymorphisms would not have influences on eradication rates of H. pylori by using sequential therapy. Copyright © 2017, The Gastroenterological Society of Taiwan, The Digestive Endoscopy Society of Taiwan and Taiwan Association for the Study of the Liver.